Cumulative Psychosocial Stress and Ideal Cardiovascular Health in Older Women: Data by Race/Ethnicity. Issue 17 (23rd April 2019) - Burroughs Peña, Melissa S.; Mbassa, Rachel S.; Slopen, Natalie B.; Williams, David R.; Buring, Julie E.; Albert, Michelle A.
Abstract : Background: Research implicates acute and chronic stressors in racial/ethnic health disparities, but the joint impact of multiple stressors on racial/ethnic disparities in cardiovascular health is unknown. Methods: In 25 062 women (24 053 white; 256 Hispanic; 440 black; 313 Asian) articipating in the Women's Health Study follow-up cohort, we examined the relationship between cumulative psychosocial stress (CPS) and ideal cardiovascular health (ICH), as defined by the American Heart Association's 2020 strategic Impact Goals. This health metric includes smoking, body mass index, physical activity, diet, blood pressure, total cholesterol, and glucose, with higher levels indicating more ICH and less cardiovascular risk (score range, 0–7). We created a CPS score that summarized acute stressors (eg, negative life events) and chronic stressors (eg, work, work-family spillover, financial, discrimination, relationship, and neighborhood) and traumatic life event stress reported on a stress questionnaire administered in 2012 to 2013 (score range, 16–385, with higher scores indicating higher levels of stress). Results: White women had the lowest mean CPS scores (white: 161.7±50.4; Hispanic: 171.2±51.7; black: 172.5±54.9; Asian: 170.8±50.6; P overall <0.01). Mean CPS scores remained higher in Hispanic, black, and Asian women than in white women after adjustment for age, socioeconomic status (income and education), and psychological status (depression and anxiety) ( P <0.01 for each). Mean ICH scores varied by race/ethnicity ( P <0.01) and were significantly lower in black women and higher in Asian women compared with white women (β-coefficient [95% CI]: Hispanics, −0.02 [−0.13 to −0.09]; blacks, −0.34 [−0.43 to −0.25]; Asians, 0.34 [0.24 to 0.45]); control for socioeconomic status and CPS did not change these results. Interactions between CPS and race/ethnicity in ICH models were not significant. Conclusions: Both CPS and ICH varied by race/ethnicity. ICH remained worse in blacks and better in Asians compared with whites, despite taking into account socioeconomic factors and CPS. Abstract : Supplemental Digital Content is available in the text.